Jesus, Trinity, and Creation: Divine Simplicity, the "Real" Relation, and Trinitarian Economy in Dialogue with Robert Jenson. Issue 3 (August 2019) - Platter, Jonathan M.
In this essay, I engage Robert Jenson ecumenically by offering a reading of his theology that gives appropriate weight to his radical identification of God's eternal being (immanent life) with God's historical acts (economy), while also arguing that his arguments have a striking point of contact with the classical denial of a real relation of God to creation. I argue that both positions share a desire to express a radical intimacy between God and creation as well as God's boundlessness and simplicity. The benefit of this comparative study is that it illuminates potential commonalities between Jenson's revisionary metaphysics and one aspect of "classical" metaphysics. The recognition of such metaphysical common ground provides opportunity for mutual enrichment.